Pengaruh Kemampuan Manajerial Kepala Sekolah terhadap Kinerja Guru Sekolah Dasar di Gugus Lampeuneurut Aceh Besar - Budiati, Kartiningsih; Musdiani, Musdiani; Putra, Mulia (LPPM Institut Pendidikan Nusantara Global, 2024)
The quality of education in an area is influenced by various factors, including teacher performance. Teachers must work professionally to develop outstanding students. Teacher performance is believed to be related to the principal's leadership abilities. The aim of this research is to determine the influence of school principal management skills on the performance of elementary school teachers in the Lampenurut Aceh Besar cluster. This research is a type of correlational research. The research was conducted in elementary schools in Aceh Besar district. The populations of this study were all teachers who taught in elementary schools in the Lampenurut Aceh Besar cluster. The sample was then taken through a proportional random sample of 156 teachers. Data was collected using a questionnaire distributed to respondents. The questionnaire contains the principal's management skills and teacher performance. Research variables were measured using a Likert scale. The data obtained was then tested using the Pearson product-moment correlation test using the SPSS 26 program. The research results showed that the average management ability of school principals was moderate. This can be seen in the competence of school principals in the planning, implementation, organizing/management, and supervision processes. Likewise, the average teacher performance is also in the middle category. Teacher performance is evaluated using three indicators, namely planning, implementation, and learning assessment. The results of statistical tests show that the principal's leadership influences the performance of elementary school teachers in Lampenurut District. The better the principal's management skills, the better the teacher's performance, and vice versa.